Środowiskowe uwarunkowania osadnictwa pradziejowego i wczesnośredniowiecznego w północnej części Borów Tucholskich - Grzelakowska, Elżbieta (Acta Universitatis Lodziensis. Folia Archaeologica, 1989)
The dissimilanity of development in economy and setlement in the northern part of Tuchola Forest in relation to generally accepted scheme for Polish Lands was stated in the paper. This dissimilarity does not result from economic under-development of the discussed territories but from the perfect adaptation of local population to possibilities created by natural environment. Some "delay" in applying new ways of farming was caused by ecologic conditioning which for the whole time was determinent for forms and economic and settlement level in the northern part of Tuchola Forest.